Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Heteropoly acid encapsulated SBA-15/TiO(2) nanocomposites and their unusual performance in acid-catalysed organic transformations - Sawant, Dhanashri P.; Justus, Josena; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Srinivasu, Pavuluri; Velmathi, Sivan; Halligudi, Shivappa B.; Vinu, Ajayan (Chemistry-A European Journal, 2008)
The preparation of SBA-15/TiO(2) nanocomposites with different loadings of Keggin-type 12-tungsto-phosphoric acid (TPA) nanocrystals in their mesochannels through a simple and effective vacuum impregnation method is reported for the first time. The catalysts have been characterised by various sophisticated techniques, including XRD, HRSEM, and TEM. It has been found that the acidity and the textural parameters of the nanocomposites can be controlled by simply changing the loadings of TPA and TiO(2) or the calcination temperature. TPA and TiO(2) loadings of 15 and 22.4 wt %, respectively, and a calcination temperature of 1123 K have proved to be optimal for obtaining mesoporous nanocomposite materials with the highest acidity. Moreover, the activities of these catalysts in promoting hydroamination as well as Mannich and Claisen rearrangement reactions have been extensively investigated. The results show that the amount of TPA has a great influence on the activity of the nanocomposites in all of the reactions studied. The effects of other reaction parameters, such as temperature and reaction time, on the conversion and product selectivity have also been studied in detail. A kinetic analysis of the formation of the products under various reaction conditions is presented. It has been found that the activity of the nanocomposite composed of 15 wt % TPA deposited on 22.4 wt of TiO(2) on SBA-15 in promoting the studied reaction is remarkably higher than the catalytic activities shown by pure TPA, TiO(2)-loaded SBA-15, or TPA-loaded SBA-15. The results obtained have indicated that the acidity and the structural control of the nanocomposite materials are highly critical for obtaining excellent catalytic activity, and the presented highly acidic nanocomposites are considered to show great potential for use as catalysts in promoting many acid-catalysed organic transformations.
Keywords: Bronsted acids; mesoporous materials; nanoreactors; nanotechnology; supported catalysts

Highly efficient and chemo selective catalyst system for the synthesis of blossom orange fragrance and flavoring compounds - Justus, Josena; Vinu, Ajayan; Devassy, Biju M.; Balasubramanian, Veerappan V.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
{Acetal and acylal formation reactions of organic compounds are efficiently catalyzed by zirconia-supported mixed oxide systems under liquid-phase reaction conditions. 15WZ-750 (where
Keywords: Acetal; acylal; Silicotungstic acid; tungsten oxide; tungstophosphoric acid; Zirconia